Corn silage and poultry litter for dairy heifers during the dry season - Faria, Paulo Fernando L.; Carvalho, Eline Menezes R. de; Lima, Carlos Rodrigues; Carvalho, Sylvio Romero de (Pesquisa Agropecuaria Brasileira, 2014)
Fifteen crossbred dairy heifers were assigned to three groups, receiving (1) corn silage only (2) corn silage supplemented with a mixture of poultry litter and com flour (1,425 and 1,396 grams respectively per animal per day), and (3) mollasses grass pasture only. The animals selected were twenty month old and had approximately 220 kg of weight each. The trial was conducted during the dry season and covered a 112 day-period. Treatment effects were evaluated through the gains or losses of live weight. Daily gains were 528 g for animals receiving com silage plus a mixture of poultry litter and corn flour, and 195 g for those fed on a molasses grass pasture. Animals fed only silage lost 175 g per animal per day.